(untitled) (mathematica didactica, 2013)
Spatial perspective taking has been studied a lot with children as well as with adults. But the symmetry of the objects has not been considered in these surveys. Therefore, this aspect has been varied systematically in an interview study with children at the beginning of schooling. Against our expectation, the assumption that symmetry increases the difficulty could not be confirmed concerning the number of correct answers, but is reflected in the types of errors.